The relative importance of competition to contagion: Evidence from the digital currency market - Peng Xie; Jiming Wu; Hongwei Du (Financial Innovation, 2019)
How does the valuation change of an industry leader influence its competitors? Does it induce a competitive effect or a contagion effect? What are the driving forces of such influences? We attempted to answer these questions within digital currency markets. We found that both close and distant competitors against an industry leader experience high competitive effects, while moderate competitors experience high contagion effects. Next, we empirically demonstrated how this U-shaped pattern reduces to a linear relationship depending on the industry concentration. Lastly, we identified eight distinct information categories from a social media platform of the industry leader and compared the influence of the eight information categories on the industry leader's competitors. Our analysis suggests that the relative importance of the competitive effect to the contagion effect in the industry depends on the category of the information.
Keywords: 650; Social media; Contagion; Competition; Information spillover; Digital economy